Interferensi Fonologi Bahasa Jepang Terhadap Bahasa Indonesia Oleh Youtuber Yusuke (Wasedaboys) - Patmi, Ni Putu Dita Candra; Pradnyana, Ida Bagus Made Pramana; Hermawan, Gede Satya (KIRYOKU, 2025)
Japanese YouTuber (non-Indonesian speaker) who tries to speak Indonesian has a different pronunciation from Indonesian. Therefore, this research was conducted using a descriptive method, which involved listening to video blog, collecting data using note-taking and sorting techniques, analyzing the data, and concluding using Weinreich’s theory. Weinreich’s theory is used to analyze the data obtained. Therefore, the results obtained are in the form of speakers changing the phoneme /l/ to /ɾ/ amounts to 12 data, the speaker pronounces with tongue vibrates at the back of the upper teeth, and air is forced through the oral cavity, producing a sound known as trilling. Changing the phoneme /ŋ/ to /n and /m/ amounts to 2 data pronounced by pressing the lips together so air can escape through the nose. And changing the phoneme /ə/ to /ɯ/ amounts to 5 data, the speaker pronounces it by looking for the closest phoneme, namely /ɯ/, and even pronouncing /ə/ sounds more like the sound /ɯ/. From this analysis, speakers experienced phonological interference, which turned out to be that their mother tongue, Japanese could influence their second language, Indonesian.